Graphene-hydroxyapatite composite material, preparation method thereof, desulfurizer and heavy metal adsorbent
Through the preparation of graphene-hydroxyapatite composite materials, the oxides of zinc and silver are loaded with hydroxyapatite, and the coating of graphene oxides, the problems of uneven dispersion and unfavorable regeneration and use of adsorbents are solved, and the problem of uneven dispersion of adsorbents is achieved. It can effectively remove sulfur-containing compounds in diesel.
Patent Information
- Application Number
- CN202411693044.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
In the existing adsorption and desulfurization technology, the active sites are unevenly dispersed, resulting in unfavorable regeneration and use of adsorbents, and it is difficult to effectively remove inactive sulfur-containing compounds with high stability in diesel.
The graphene-hydroxyapatite composite material is used to support zinc and silver oxides through hydroxyapatite as a support, and the dispersion and regeneration of the material are improved by coating of graphene oxide.
The adsorption efficiency and regenerative properties of graphene-hydroxyapatite composite materials are improved, and the sulfur-containing compounds in diesel can be effectively removed, including inactive sulfur-containing compounds with high stability.
Smart Images

Figure CN119461353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material synthesis, and more specifically to a graphene-hydroxyapatite composite material and a preparation method thereof, a desulfurizing agent and a heavy metal adsorbent. Background Art
[0002] Fossil fuel is a mixture of hydrocarbons or hydrocarbon derivatives, including natural resources such as coal, oil and natural gas. As an important fuel, diesel is widely used as a power source for vehicles, ships and internal combustion engine equipment due to its large volume calorific value, high efficiency and good power performance. However, untreated diesel contains many sulfur compounds, which will produce sulfur oxides after combustion, which will not only cause irreversible corrosion and damage to engine parts, but also directly emit into the air and combine with water to form acid rain, which will not only destroy the growth of vegetation, but also reduce the life of buildings, cultural heritage and industrial equipment. Sulfur oxides will also reduce the catalytic activity of motor vehicle exhaust treatment catalysts due to poisoning, thereby increasing the emission of nitrogen oxides and particulate matter in the air, aggravating the pollution of the urban environment and endangering human health. Diesel contains a variety of sulfides, mainly mercaptans, sulfides, thiophenes, benzothiophenes, dibenzothiophenes and their derivatives. Thiophene compounds have a higher sulfur content, accounting for more than 80% of the total sulfur content of diesel. Among the thiophene compounds, benzothiophene and dibenzothiophene have the highest content, accounting for 70% or even more of the thiophene compounds. Among them, active sulfur-containing substances such as sulfur element, hydrogen sulfide, mercaptans, and sulfides have a low boiling point and are chemically active. They can generally be removed by commonly used industrial technical means, while inactive sulfur-containing compounds such as thiophene, benzothiophene, and dibenzothiophene have relatively stable chemical properties and are more difficult to remove.
[0003] Adsorption desulfurization is a method that removes sulfur compounds from fuel oil by adsorbing sulfur compounds onto the adsorbent under mild conditions without the need for hydrogen. The metal active components form chemical bonds with the sulfides in the fuel oil, thereby removing the sulfides. Researchers have studied adsorbents, such as using SBA-15 mesoporous molecular sieves as carriers, but the active sites are not evenly dispersed and easily lost, which is not conducive to the regeneration of the adsorbent. Summary of the invention
[0004] In view of the above problems, the present invention provides a graphene-hydroxyapatite composite material and a preparation method and application thereof. During the preparation process, hydroxyapatite is used as a carrier, transition metal zinc and silver are introduced, which solves the problem of uneven dispersion of active sites. Then, graphene oxide is coated to reduce the loss of transition metal zinc and silver, thereby improving the service life of the graphene-hydroxyapatite composite material.
[0005] The first object of the present invention is to provide a method for preparing a graphene-hydroxyapatite composite material, comprising the following steps:
[0006] In an alcohol organic solvent, polyethyleneimine is used as a modifier to graft hydroxyapatite to obtain amino hydroxyapatite.
[0007] The aminated hydroxyapatite is dispersed in water, a zinc precursor and a silver precursor are added, the pH is adjusted to 9-10, and after stirring evenly, a hydrothermal reaction is carried out at 120° C. to 130° C. to prepare zinc-silver loaded hydroxyapatite; for example, the pH is adjusted to 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10, etc.; but it is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0008] The hydrothermal temperature is 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C, 130°C, etc.; but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0009] The zinc-silver loaded hydroxyapatite composite material is added into a graphene oxide solution, and an electrostatic self-assembly reaction is carried out at room temperature to obtain a graphene-hydroxyapatite composite material.
[0010] In a preferred embodiment of the present invention, the mass ratio of the aminated hydroxyapatite to the zinc precursor and the silver precursor is 0.1-0.15:1-4, and the mass ratio of the zinc precursor to the silver precursor is 1-4:0.3-0.4.
[0011] For example, the mass ratio of aminated hydroxyapatite and zinc precursor is 0.1:1, 0.1:2, 0.1:3, 0.1:4, 0.12:1, 0.12:2, 0.12:3, 0.12:4, 0.13:1, 0.13:2, 0.13:3, 0.13:4, 0.14:1, 0.14:2, 0.14:3, 0.14:4, 0.15:1, 0.15:2, 0.15:3, 0.15:4, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0012] For example, the mass ratio of the zinc precursor to the silver precursor is 1:0.3, 1:0.32, 1:0.34, 1:0.36, 1:0.38, 1:0.4, 2:0.3, 2:0.32, 2:0.34, 2:0.36, 2:0.38, 2:0.4, 3:0.3, 3:0.32, 3:0.34, 3:0.36, 3:0.38, 3:0.4, 4:0.3, 4:0.32, 4:0.34, 4:0.36, 4:0.38, 4:0.4, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0013] In a preferred embodiment of the present invention, the reaction time of the hydrothermal reaction is 10 h to 12 h. For example, the reaction time of the hydrothermal reaction is 10 h, 10.5 h, 11 h, 11.5 h, 12 h, etc., but is not limited to the listed values. Other unlisted values within the above numerical range are also applicable.
[0014] In a preferred embodiment of the present invention, the mass ratio of the zinc-silver loaded hydroxyapatite composite material and graphene oxide is 8:1-7. For example, the mass ratio of the zinc-silver loaded hydroxyapatite composite material and graphene oxide is 8:1, 4:1, 8:3, 2:1, 8:5, 4:3, 8:7, etc., but is not limited to the listed values. Other values not listed within the above numerical range are also applicable.
[0015] In a preferred embodiment of the present invention, the reaction time of electrostatic self-assembly is 5 min to 15 min, and the reaction time of electrostatic self-assembly is 5 min, 7 min, 9 min, 11 min, 13 min, 15 min, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0016] In a preferred embodiment of the present invention, the mass ratio of polyethyleneimine to hydroxyapatite is 1:5-6. For example, the mass ratio of polyethyleneimine to hydroxyapatite is 1:5, 1:5.2, 1:5.4, 1:5.6, 1:5.8, 1:6, etc., but is not limited to the listed values. Other unlisted values within the above numerical range are also applicable.
[0017] In a preferred embodiment of the present invention, the reaction time of the grafting treatment is 30 min to 40 min. For example, the reaction time of the grafting treatment is 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc., but is not limited to the listed values. Other unlisted values within the above numerical range are also applicable.
[0018] The second object of the present invention is to provide a graphene-hydroxyapatite composite material prepared by the above preparation method.
[0019] The third object of the present invention is to provide a desulfurizer, which comprises the above-mentioned graphene-hydroxyapatite composite material.
[0020] The fourth object of the present invention is to provide a heavy metal adsorbent, which comprises the above-mentioned graphene-hydroxyapatite composite material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention provides a graphene-hydroxyapatite composite material. During the preparation process, hydroxyapatite has a porous structure and can be used as a carrier to better load zinc and silver oxides. Due to the porous structure, the zinc and silver oxides have a better dispersion effect. Then, a layer of graphene oxide is introduced. Due to the presence of amino groups on the amino hydroxyapatite, the graphene oxide is easy to generate hydrogen bonds through an electrostatic self-assembly reaction, so that it is coated on the hydroxyapatite loaded with zinc and silver to prepare a graphene-hydroxyapatite composite material. The graphene-hydroxyapatite composite material prepared by the present invention is used as a desulfurizer. When the reaction mixture is reacted with hydroxyapatite, the oxides of zinc and silver act as active centers, and the oxides of transition metals zinc and silver provide empty orbitals for the lone pair of electrons of the S atom on the dibenzothiophene molecule. The S in dibenzothiophene forms a π-complex adsorption with the transition metal. At the same time, graphene oxide and dibenzothiophene form a π-π interaction to improve the adsorption efficiency. In addition, the loading of hydroxyapatite and the coating of graphene oxide reduce the loss of transition metal oxides of zinc and silver, thereby improving the regeneration of the graphene-hydroxyapatite composite material. The synergistic effect between hydroxyapatite, zinc oxide, silver and graphene oxide can effectively remove sulfur-containing compounds.
[0023] (2) The graphene-hydroxyapatite composite material prepared by the present invention can be used to adsorb heavy metal ions. The ion exchange and adsorption capacity of hydroxyapatite can effectively adsorb nickel ions. Then, the introduction of graphene oxide allows the carboxyl and hydroxyl groups on the surface of graphene oxide to be used for adsorbing nickel ions. Graphene oxide provides a larger surface area and more adsorption sites, which is more conducive to the adsorption of nickel. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The desulfurization rate over time of adding the graphene-hydroxyapatite composite material prepared in Example 3 to diesel of different concentrations.
[0025] Figure 2 Desulfurization rates of graphene-hydroxyapatite composite materials prepared in different embodiments and comparative examples.
[0026] Figure 3Desulfurization rate of graphene-hydroxyapatite composite material and simulated diesel at different ratios.
[0027] Figure 4 This is the recycling performance of the graphene-hydroxyapatite composite material prepared in Example 3.
[0028] Figure 5 This is the chromium removal rate of the graphene-hydroxyapatite composite material prepared in Example 3.
[0029] Figure 6 Nickel removal rate of the graphene-hydroxyapatite composite material prepared in Example 3. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Graphene is an allotrope of carbon, with carbon atoms arranged in sp 2 Hybrid bonding forms a single-layer hexagonal honeycomb lattice graphene. Graphene's crystal structure can be used to construct fullerenes, graphene quantum dots, carbon nanotubes, nanobelts, multi-walled carbon nanotubes and nanohorns. Stacked graphene layers (greater than 10 layers) form graphite, which is held together by van der Waals forces, with a crystal plane spacing of 0.335 nanometers. Graphene has excellent optical, electrical and mechanical properties.
[0032] The chemical composition of hydroxyapatite is Ca 10 (PO4)6(OH)2, the calcium-phosphorus ratio is 1.67. Hydroxyapatite crystals are hexagonal, showing six-sided columns, and the unit cell contains 10 Ca 2+ , 6 PO4 3- and 2 OH - As the main inorganic component of bone tissue, hydroxyapatite has excellent osteoconductivity, biocompatibility and ion exchange properties.
[0033] The graphene-hydroxyapatite composite materials prepared in the prior art are mainly used in the fields of biomedicine, material enhancement, biosensors, and 3D printing. For example, graphene-hydroxyapatite composite materials can be used as bone transplant substitutes for bone repair. It not only retains the biological activity and biocompatibility of hydroxyapatite, which is conducive to the growth of new bones and the combination with human tissue, but also improves the overall strength of the material with the help of the excellent mechanical properties of graphene, which can meet the mechanical requirements in the bone repair process and promote the regeneration and repair of bone tissue. When the graphene-hydroxyapatite composite material is used as a drug carrier to deliver drugs, the large specific surface area and unique structure of graphene enable it to load drugs, and hydroxyapatite increases the biocompatibility and stability of the material. Graphene-hydroxyapatite composite materials are added to other polymer materials, ceramic materials or metal materials as a reinforcing agent to improve the mechanical properties, thermal properties and electrical conductivity of the material. Graphene-hydroxyapatite composite materials are used to prepare biosensors to detect various substances in the body.
[0034] In order to solve the problems existing in the adsorbent used for adsorption desulfurization in the background technology, the present invention proposes a method for preparing a graphene-hydroxyapatite composite material, comprising the following steps:
[0035] In an alcohol organic solvent, polyethyleneimine is used as a modifier to graft hydroxyapatite to obtain amino hydroxyapatite.
[0036] The aminated hydroxyapatite is dispersed in water, a zinc precursor and a silver precursor are added, the pH is adjusted to 9-10, and after being stirred evenly, a hydrothermal reaction is carried out at 120° C. to 130° C. to prepare zinc-silver loaded hydroxyapatite.
[0037] The zinc-silver loaded hydroxyapatite composite material is added into a graphene oxide solution, and an electrostatic self-assembly reaction is carried out at room temperature to obtain a graphene-hydroxyapatite composite material.
[0038] In the preparation process, first, polyethyleneimine is used to perform surface functionalization treatment on hydroxyapatite. Polyethyleneimine is introduced on the surface of hydroxyapatite to improve the dispersibility of hydroxyapatite and reduce the aggregation of hydroxyapatite. At the same time, after the grafting treatment, the surface of hydroxyapatite is provided with amino groups. The introduction of amino groups facilitates the subsequent loading of other nanomaterials. 2+ , the silver precursor provides Ag + , under the condition of pH 9 to 10, a hydrothermal reaction is carried out to prepare zinc and silver oxides on hydroxyapatite / graphene oxide to prepare zinc-silver loaded hydroxyapatite. Graphene oxide contains functional groups such as hydroxyl and carboxyl groups, which react with amino hydroxyapatite through electrostatic self-assembly to form hydrogen bonds, thereby preparing a graphene-hydroxyapatite composite material.
[0039] The preparation method of hydroxyapatite used in the present invention is as follows:
[0040] Step 1. Dissolve 2 mmol Ca(NO3)2·4H2O in 15 ml of deionized water and stir for 30 min. Then add 1.46 g C6H5Na3O7·2H2O and stir for 1 h. Mark it as the first solution.
[0041] Step 2: Weigh 0.363 g of CTAB and add it to 20 ml of deionized water. Stir it thoroughly for 30 min in a constant temperature water bath at 30°C until the solution becomes clear. Then add 0.16 g of (NH4)2HPO4 and stir it thoroughly for 30 min. Then, absorb 2 mol / L HNO3 to adjust the pH value to 5. This solution is marked as the second solution.
[0042] Step 3: Add the first solution dropwise to the second solution, stir thoroughly for half an hour, then slowly pour the mixed solution into a 100 ml polytetrafluoroethylene-lined autoclave, and react in a 180°C homogeneous reactor for 24 hours. After the autoclave is cooled to room temperature, remove and open the autoclave, and wash the precipitate with deionized water and anhydrous ethanol and centrifuge it three times. Place the obtained powder in a 60°C constant temperature blast drying oven for drying to obtain hydroxyapatite, which is recorded as HA.
[0043] The polyethyleneimine used in the present invention has an average molecular weight of 100,000 and is purchased from Shanghai MacLean Biochemical Technology Co., Ltd. The present invention has no particular limitation on the source of polyethyleneimine, and those skilled in the art can purchase it through commercial channels according to actual application conditions, product quality and product performance.
[0044] The graphene oxide used in the present invention has a sheet diameter of 0.5 μm to 5 μm and a thickness of 0.8 nm to 1.2 nm, and is purchased from Shanghai MacLean Biochemical Technology Co., Ltd. The present invention has no particular restriction on the source of graphene oxide, and those skilled in the art can purchase it through commercial channels according to actual application conditions, product quality and product performance, or can prepare it through existing preparation methods.
[0045] Example 1
[0046] This embodiment provides a method for preparing a graphene-hydroxyapatite composite material, comprising the following steps:
[0047] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0048] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.3 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0049] Step 3, add 0.01g of graphene oxide to 100ml of anhydrous ethanol, stir at 5°C for 4h to obtain a graphene oxide solution, then add 0.08g of zinc-silver loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30°C for 10min, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-(Zn-Ag)-GO1-a.
[0050] Example 2
[0051] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0052] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.3 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0053] Step 3, add 0.03g of graphene oxide to 100ml of anhydrous ethanol, stir at 5°C for 4h to obtain a graphene oxide solution, then add 0.08g of zinc-silver loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30°C for 10min, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-(Zn-Ag)-GO3-a.
[0054] Example 3
[0055] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0056] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.3 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0057] Step 3, add 0.05g of graphene oxide to 100ml of anhydrous ethanol, stir at 5°C for 4h to obtain a graphene oxide solution, then add 0.08g of zinc-silver loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30°C for 10min, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-(Zn-Ag)-GO5-a.
[0058] Example 4
[0059] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0060] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.3 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0061] Step 3: Add 0.07 g of graphene oxide to 100 ml of anhydrous ethanol, stir at 5 ° C for 4 hours to obtain a graphene oxide solution, then add 0.08 g of zinc-silver loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30 ° C for 10 minutes, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-(Zn-Ag)-GO7-a.
[0062] Example 5
[0063] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0064] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.2 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0065] Step 3, add 0.05g of graphene oxide to 100ml of anhydrous ethanol, stir at 5°C for 4h to obtain a graphene oxide solution, then add 0.08g of zinc-silver loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30°C for 10min, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-(Zn-Ag)-GO5-b.
[0066] Example 6
[0067] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0068] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.4 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0069] Step 3: Add 0.05 g of graphene oxide to 100 ml of anhydrous ethanol, stir at 5 ° C for 4 hours to obtain a graphene oxide solution, then add 0.08 g of zinc-silver-loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30 ° C for 10 minutes, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-(Zn-Ag)-GO5-c.
[0070] Example 7
[0071] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0072] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.1 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0073] Step 3, add 0.05g of graphene oxide to 100ml of anhydrous ethanol, stir at 5°C for 4h to obtain a graphene oxide solution, then add 0.08g of zinc-silver loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30°C for 10min, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-(Zn-Ag)-GO5-d.
[0074] Example 8
[0075] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.3 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0076] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.4 g of Zn(NO3)2·6H2O and 0.04 g of Ag(NO3)2, adjust the pH to 10, stir evenly, transfer to a hydrothermal reactor, and react at 130°C for 12 h to obtain zinc-silver loaded hydroxyapatite.
[0077] Step 3: Add 0.01 g of graphene oxide to 100 ml of anhydrous ethanol, stir at 5 ° C for 4 hours to obtain a graphene oxide solution, then add 0.08 g of zinc-silver-loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30 ° C for 5 minutes, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material.
[0078] Example 8
[0079] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.28 g of hydroxyapatite, and ultrasonically disperse for 30 min. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0080] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.1 g of Zn(NO3)2·6H2O and 0.035 g of Ag(NO3)2, adjust the pH to 9.5, stir evenly, transfer to a hydrothermal reactor, and react at 125°C for 11 h to obtain zinc-silver loaded hydroxyapatite.
[0081] Step 3: Add 0.07 g of graphene oxide to 100 ml of anhydrous ethanol, stir at 5 ° C for 4 hours to obtain a graphene oxide solution, then add 0.08 g of zinc-silver-loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30 ° C for 15 minutes, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material.
[0082] Comparative Example 1
[0083] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0084] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.1 g of Zn(NO3)2·6H2O, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-loaded hydroxyapatite.
[0085] Step 3: Add 0.05 g of graphene oxide to 100 ml of anhydrous ethanol, stir at 5 ° C for 4 hours to obtain a graphene oxide solution, then add 0.08 g of zinc-silver-loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30 ° C for 10 minutes, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-Zn-GO5-c.
[0086] Comparative Example 2
[0087] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0088] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain silver-loaded hydroxyapatite.
[0089] Step 3: Add 0.05 g of graphene oxide to 100 ml of anhydrous ethanol, stir at 5 ° C for 4 hours to obtain a graphene oxide solution, then add 0.08 g of zinc-silver-loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30 ° C for 10 minutes, and after standing, centrifuge, filter and dry to obtain a graphene-hydroxyapatite composite material; recorded as HA-Ag-GO5-c.
[0090] Comparative Example 3
[0091] Step 1: Add 0.05 g of polyethyleneimine to 100 mL of anhydrous methanol, stir at 300 r / min at room temperature until the polyethyleneimine is dissolved, weigh 0.25 g of hydroxyapatite, and ultrasonically disperse it for 30 minutes. After the ultrasonication, centrifuge, filter, and dry to obtain amino hydroxyapatite.
[0092] Step 2: Add 0.01 g of amino hydroxyapatite to 70 mL of anhydrous ethanol, and after ultrasonic dispersion for 30 min, add 0.1 g of Zn(NO3)2·6H2O and 0.03 g of Ag(NO3)2, adjust the pH to 9, stir evenly, transfer to a hydrothermal reactor, and react at 120°C for 10 h to obtain zinc-silver loaded hydroxyapatite.
[0093] Step 3: Add 0.05 g of graphene oxide to 100 ml of anhydrous ethanol, stir at 5 ° C for 4 hours to obtain a graphene oxide solution, then add 0.08 g of zinc-silver loaded hydroxyapatite to the above graphene oxide solution, let it stand at 30 ° C for 10 minutes, and after standing, centrifuge, filter and dry to obtain a hydroxyapatite composite material; recorded as HA-(Zn-Ag).
[0094] N2 isothermal adsorption-desorption analysis was performed using a Micromeritics ASAP 2020HD88 physical adsorption instrument to test the N2 isothermal adsorption and desorption of the samples. The BET equation was used to calculate the specific surface area to characterize the specific surface area of the samples.
[0095] Table 1 Physical properties of different materials
[0096] <![CDATA[Specific surface area (m 2 / g)]]> HA 23.734±0.047 Example 1 28.678±0.064 Example 2 29.541±0.038 Example 3 32.527±0.051 Example 4 30.174±0.042 Example 5 31.346±0.035 Example 6 31.981±0.073 Example 7 30.463±0.066
[0097] It can be seen from Table 1 that, compared with HA, the specific surface area of the graphene-hydroxyapatite composite material prepared according to the preparation method of the present invention is increased, and the increase in the specific surface area is beneficial to improving the adsorption capacity of the material.
[0098] Dibenzothiophene was used to prepare simulated diesel for testing. Specifically, 1000 mL of isooctane was added as a solvent into a conical flask, and dibenzothiophene was added and stirred until uniformly mixed to obtain simulated diesel with an initial sulfur concentration of 400 μg / g, 1000 μg / g or 2000 μg / g.
[0099] The present invention adopts a static adsorption method to measure the saturated adsorption capacity of the graphene-hydroxyapatite composite material to evaluate its adsorption desulfurization performance, and examines the regeneration performance of the adsorbent after regeneration.
[0100] The static adsorption method is to place a certain proportion of desulfurizer and diesel in a container at a certain temperature, soak for a period of time, filter out the adsorbent, and determine the sulfur content of the diesel. The specific operation steps are: weigh 1g of simulated diesel with an initial sulfur concentration of 400μg / g, 1000μg / g or 2000μg / g, put it in a flask, and then put 0.1g of graphene-hydroxyapatite composite material, stir and adsorb at room temperature for 20min, 40min, 60min, 80min, 100min and 120min. After the adsorption is completed, stop stirring, centrifuge and separate the graphene-hydroxyapatite composite material and supernatant after adsorption of dibenzothiophene, take about 1.0mL of simulated diesel from the supernatant as a gas chromatography detection sample, analyze its remaining sulfur content, and compare it with the initial sulfur content.
[0101] The gas chromatograph model and specifications are: Agilent 19091N-233, 30.0m×250um×0.50um. ), nitrogen as carrier gas, injection volume of 0.4μL; vaporization chamber temperature of 220℃; split ratio of 50:1; detector temperature of 250℃; program heating process of 60℃ for 2min, heating to 100℃ at 10℃ / min, and holding for 1min; residence time of 4.7min; stop time of 11min; FPD detection limit of 1μg-S / g.
[0102] The desulfurization rate is calculated according to the following formula.
[0103]
[0104] Where η1 is the desulfurization rate, %; C0 is the initial concentration of simulated diesel, mg-S / g; C e It is the concentration after simulating diesel adsorption equilibrium, mg-S / g.
[0105] The specific steps for testing the regeneration performance are as follows: the recovered composite material is washed with ethanol three times, the washed adsorbent is vacuum dried at 100°C for 12 hours, and then the dried composite material is placed in a tubular furnace, heated to 350°C at a heating rate of 5°C / min under a flow rate of N2 atmosphere, purged for 2 hours, and high-temperature desorption regeneration is performed. The regenerated graphene-hydroxyapatite composite material repeats the above adsorption-regeneration operation steps, and the cycle is repeated a certain number of times to examine the change in the saturated adsorption capacity of the adsorbent.
[0106] The present invention uses the graphene-hydroxyapatite composite material prepared in Example 3 to study the desulfurization performance under different sulfur contents. When the ratio of the graphene-hydroxyapatite composite material to the simulated diesel is 1g:10mL, at room temperature, the concentration of the simulated diesel is changed to 400μg / g, 1000μg / g and 2000μg / g, and the change of the desulfurization rate over time is investigated. Figure 1 It can be seen that when the initial sulfur content is 400 μg / g and the reaction time is 80 min, the desulfurization rate reaches 90.17%. When the time is extended to 120 min, the desulfurization rate reaches 93.59%. When the initial sulfur content is increased to 1000 μg / g and the adsorption time is 120 min, the desulfurization rate reaches 89.6%. When the initial sulfur content continues to increase to 2000 μg / g and the adsorption time is 120 min, the desulfurization rate can still reach 78.37%. As the initial sulfur content increases, the desulfurization rate decreases. This may be due to the desulfurization of dibenzothiophene after the graphene-hydroxyapatite composite material is adsorbed saturated. However, even if the initial sulfur content increases, the graphene-hydroxyapatite composite material prepared by the present invention still has a high desulfurization rate and can effectively remove sulfur-containing compounds in diesel.
[0107] When the initial sulfur content in the simulated diesel was 400 μg / g and the ratio of the graphene-hydroxyapatite composite material to the simulated diesel was 1 g:10 mL, the desulfurization rates of the graphene-hydroxyapatite composite materials prepared in different embodiments and comparative examples were investigated under the condition of adsorption for 120 min at room temperature. Figure 2 As shown, it can be seen from Examples 1 to 4 that with the increase in the amount of graphene oxide added, when the amount of graphene oxide added is 0.05g, the graphene-hydroxyapatite composite material prepared therefrom has the highest desulfurization rate for dibenzothiophene in simulated diesel. When the amount of fixed graphene oxide added is 0.05g, as in Example 3 and Implementations 5-7, with the amount of Zn(NO3)2·6H2O added increasing to 0.3g, the graphene-hydroxyapatite composite material prepared therefrom has the highest desulfurization rate for dibenzothiophene in simulated diesel. This is because the specific surface area of the graphene-hydroxyapatite composite material increases, which increases the adsorbable sites of the graphene-hydroxyapatite composite material, thereby improving the adsorption of dibenzothiophene.
[0108] Compared with Example 3, the graphene-hydroxyapatite composite material prepared in Comparative Example 1 lacks zinc oxide, the graphene-hydroxyapatite composite material prepared in Comparative Example 2 lacks silver oxide, and the hydroxyapatite prepared in Comparative Example 3 lacks graphene oxide. The desulfurization rate of the graphene-hydroxyapatite composite material prepared in Example 3 is significantly improved. This is because the desulfurization rate of dibenzothiophene and the graphene-hydroxyapatite composite material is improved through π-complex adsorption and π-π interaction, and the presence of graphene oxide reduces the loss of zinc and silver oxides, so that the zinc and silver oxides serve as active centers to improve the adsorption of dibenzothiophene.
[0109] When the initial sulfur content in the simulated diesel was 400 μg / g, the desulfurization rates of the graphene-hydroxyapatite composite material and the simulated diesel at different ratios were investigated under the conditions of adsorption for 120 min at room temperature. Figure 3 As shown, when the ratio of graphene-hydroxyapatite composite material to simulated diesel is 1:10 and the adsorption time is 120 min, the desulfurization rate reaches 93.59%. When the ratio of graphene-hydroxyapatite composite material to simulated diesel is 1:20 and 1:30, the desulfurization rates of graphene-hydroxyapatite composite material are 84.9% and 80.1%, respectively. It can be seen that even if the addition amount of graphene-hydroxyapatite composite material is reduced, it still has a good desulfurization rate.
[0110] The recycling performance of the adsorbent is also an important parameter for measuring the performance of the adsorbent. Therefore, after the first adsorption, the simulated diesel was removed, and then the graphene-hydroxyapatite composite material prepared in Example 3 was tested for its recycling performance using a fresh initial sulfur concentration of 400 μg / g. The results are as follows: Figure 4 It is shown that the graphene-hydroxyapatite composite material prepared by the present invention remains stable during the repetitive experiment. After repeated use for 6 times, the desulfurization rate still reaches 76.77%, indicating that the loading of hydroxyapatite and the coating of graphene oxide reduce the loss of transition metal zinc and silver oxides, so that the graphene-hydroxyapatite composite material has good regeneration performance.
[0111] In addition, heavy metal ions may eventually enter the water environment due to diesel combustion, diesel leakage or diesel waste, which may cause harm to the water environment. For example, researchers have detected the presence of nickel and chromium in the surface soil of Antarctica, which is speculated to be related to diesel combustion or leakage. The graphene-hydroxyapatite composite material prepared in Example 3 of the present invention is added to wastewater containing heavy metal ions to investigate the removal effect of the graphene-hydroxyapatite composite material on heavy metal ions.
[0112] A solution of potassium dichromate (K2Cr2O7) was prepared to simulate chromium-containing wastewater, and the removal effect of graphene-hydroxyapatite composite materials on heavy metal ion chromium was studied. Specifically, 0.2 g of graphene-hydroxyapatite composite material was added to 100 mL of chromium-containing wastewater with a concentration of 40 mg / L or 100 mg / L. After mixing evenly, the mixture was adsorbed at 40°C for 1 h, and then centrifuged at 2000 r / min for 5 min. Finally, the supernatant was taken to measure the remaining chromium concentration.
[0113] NiSO4·6H2O solution was prepared to simulate nickel-containing wastewater, and the removal effect of graphene-hydroxyapatite composite materials on heavy metal ion nickel was studied. Specifically, 0.2 g of graphene-hydroxyapatite composite material was added to 100 mL of nickel-containing wastewater with a concentration of 40 mg / L or 100 mg / L. After mixing evenly, the mixture was adsorbed at 40°C for 1 h, and then centrifuged at 2000 r / min for 5 min. Finally, the supernatant was taken to measure the residual nickel concentration.
[0114] The removal rate of heavy metal ions is calculated according to the following formula:
[0115]
[0116] Wherein, η2 is the heavy metal ion removal rate, %; C1 is the heavy metal ion concentration of the solution before the reaction, mg / L; C0 is the Cr(VI) concentration in the solution after the reaction, mg / L.
[0117] from Figure 5 and Figure 6 It can be seen that compared with Comparative Example 3, the graphene-hydroxyapatite composite material prepared in Example 3 has excellent removal effects on both chromium and nickel. This is because the presence of graphene oxide provides a larger specific surface area and thus provides adsorption sites, and the carboxyl and hydroxyl groups on the surface of graphene oxide can effectively adsorb nickel ions and chromium ions. When the heavy metal ion concentration is increased from 40 mg / L to 100 mg / L, the graphene-hydroxyapatite composite material prepared in Example 3 still has a better removal effect on nickel ions and chromium ions, indicating that the graphene-hydroxyapatite composite material prepared in the present invention can effectively remove nickel ions and chromium ions in wastewater.
[0118] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0119] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a graphene-hydroxyapatite composite material, characterized in that: The following steps are involved: In an alcohol organic solvent, polyethyleneimine is used as a modifier to graft hydroxyapatite to obtain amino hydroxyapatite. Dispersing aminated hydroxyapatite in water, adding a zinc precursor and a silver precursor, adjusting the pH to 9-10, stirring evenly, and performing a hydrothermal reaction at 120° C. to 130° C. to prepare zinc-silver loaded hydroxyapatite; The zinc-silver loaded hydroxyapatite composite material is added into a graphene oxide solution, and an electrostatic self-assembly reaction is carried out at room temperature to obtain a graphene-hydroxyapatite composite material.
2. According to the method for preparing a graphene-hydroxyapatite composite material according to claim 1, the mass ratio of the aminated hydroxyapatite to the zinc precursor is 0.1-0.15:1-4; the mass ratio of the zinc precursor to the silver precursor is 1-4:0.3-0.
4.
3. According to the method for preparing a graphene-hydroxyapatite composite material according to claim 1, the reaction time of the hydrothermal reaction is 10 hours to 12 hours.
4. According to the method for preparing a graphene-hydroxyapatite composite material according to claim 1, the mass ratio of the zinc-silver loaded hydroxyapatite composite material to graphene oxide is 8:1-7.
5. According to the method for preparing a graphene-hydroxyapatite composite material according to claim 1, the reaction time of the electrostatic self-assembly is 5 min to 15 min.
6. According to the method for preparing a graphene-hydroxyapatite composite material according to claim 1, the mass ratio of polyethyleneimine to hydroxyapatite is 1:5-6.
7. According to the method for preparing a graphene-hydroxyapatite composite material according to claim 1, the reaction time of the grafting treatment is 30 min to 40 min.
8. A graphene-hydroxyapatite composite material prepared by the preparation method according to any one of claims 1 to 7.
9. A desulfurizing agent, characterized in that: Comprising the graphene-hydroxyapatite composite material as described in claim 8.
10. A heavy metal adsorbent, characterized in that: Comprising the graphene-hydroxyapatite composite material as described in claim 8.
Citation Information
Patent Citations
Fuel oil desulfurizer and preparation thereof
CN101372633A
Preparation and application of magnetic hydroxyapatite / graphene oxide adsorbent
CN104289181A
Hydroxyapatite / graphene aerogel anode and preparation method thereof
CN110745811A
Preparation method of graphene / hydroxyapatite aerogel and product thereof
CN111453718A
Adsorption desulfurization catalyst as well as preparation method and application thereof
CN116408094A